Community energy in residential sector : Exploring housing company residents’ awareness and motivations - Tuomela, Sanna; Shakeel, Shah Rukh; Yousaf, Hassan; Lukkarinen, Jani; Ruokamo, Enni; Tikkanen, Tommi (IEEE, 2025)
Community energy is essential for the green and digital transformation, legitimizing the shift to decentralized energy systems and addressing local challenges. Energy communities enable active public participation in energy consumption and production as well as improve the energy system resilience. Over the last decade, more supportive policy conditions have created a need to study public awareness and motivations for energy communities, especially in the residential sector. This study evaluates energy community awareness and motivation among Finnish housing company residents. A survey of 618 respondents reveals low familiarity with energy communities (7 % moderately familiar, 1 % members). Especially financial benefits and environmental gains drive the citizens' motivation to participate, while traditional media and personal networks are key information sources. Regression analysis shows limited socio-demographic influence on motivation. The findings highlight the need for tailored incentives and communication strategies to activate housing companies as pivotal players in the community energy sector.
Keywords: Energy management; Consumer behavior; Sociotechnical systems; Social factors; fi=Markkinointi|en=Marketing|; fi=Tuotantotalous (kauppatieteet)|en=Industrial Management|